2015
DOI: 10.1186/s12966-015-0271-8
|View full text |Cite
|
Sign up to set email alerts
|

Using a verbal prompt to increase protein consumption in a hospital setting: a field study

Abstract: BackgroundSufficient protein intake among hospitalized patients may contribute to faster recovery and a decrease in healthcare costs. Nevertheless, hospitalized patients are often found to consume too little protein. This field study explored the success of a small, inexpensive intervention adapted from the marketing literature, to encourage protein consumption among hospitalized patients.MethodsThe study was performed at a hospital where patients order food by calling to the meal service. The intervention con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Another option is to stimulate intake by 'nudging' , an example of nudging in the hospital setting was a study by van der Zanden et al In this study, call centre employees asked a patient with every meal order if they would like a dairy, or other protein-rich, product with their meal. Patients often replied positively and they increased their protein intake by this simple method [22].…”
Section: Discussionmentioning
confidence: 99%
“…Another option is to stimulate intake by 'nudging' , an example of nudging in the hospital setting was a study by van der Zanden et al In this study, call centre employees asked a patient with every meal order if they would like a dairy, or other protein-rich, product with their meal. Patients often replied positively and they increased their protein intake by this simple method [22].…”
Section: Discussionmentioning
confidence: 99%
“…The selected studies were conducted worldwide between 2010 and 2019. Most of them were conducted in Australia [10,18,24,25,30,31,34,35,38,40,41,43,46], followed by Denmark [16,21,22,28,35,39,42,44], the Netherlands [15,23,26,36], Canada [47,48], Israel [17,45], and Spain [32], Hong Kong [29],…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Belgium [37], United Kingdom [27], Iceland [20], Switzerland [19], and India [33], respectively. Six articles were intervention studies [20][21][22][23][24]28], five were randomized control trial studies [15][16][17][18][19], four were pre-post studies [10,[29][30][31], cohort studies [34,36,37,49] and pilot studies [35,[39][40][41], three were observational studies [25][26][27], cross-sectional studies [32,33,38], and quasi-experimental studies [42][43][44]. Our selection additionally comprised non-randomized control trial studies [45], mixed-method studies [46], prospective interrupted time-series studies [47], and case study approaches [48].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of verbal prompts among adults are also scarce, but the results are promising. Van der Zanden et al (2015) found that prompting hospital patients to order protein‐rich side items increased selection of the item. Ebster, Wagner, and Valis (2006) found that prompts to purchase of sides with the main meal at a restaurant resulted in greater sales.…”
Section: Introductionmentioning
confidence: 99%